Desenvolvimento de Jatropha curcas (L.) em função da procedência, sistema de cultivo e densidade - Aleixo, Valdemir (2012)
This study evaluated the development of J. curcas in relation to floor area available to each plant under different cropping systems. The experiment was conducted in the period between october 2009 and may 2011, the Toledo, Paraná. The seedlings were grown in a greenhouse environment, in containers filled with commercial substrate (Plantmax®), for a period of 50 days before transplanting to the field. The experiment was established in systematic design, in factorial 3 x 4 x 5 with four replications. The treatments consisted of three provenances (DOU-Dourados, MS, JAN-Janaúba, MG; PET-Petrolina, PE), distributed in four cropping systems (WC-weed competition, GS-Growing Single, CAC-Consortium Agronomic Crops, PCH-Permanent Consortium with herb) and each with five areas useful (1.57, 4.71, 7.85, 11.00 and 14.50 m2 plant-1). Evaluations were made of the total plant height, diameter of the neck base, the canopy diameter, number of leaves, number of branches and the SPAD index at 540 days after transplant. The means were compared by Tukey test at 5% probability. For purposes of density, quantitative data were analyzed by polynomial regression at 5% probability. The Single cropping system was the most suitable for the vegetative growth of plants J. curcas. The three provenances tested were impacted by the available floor area per plant, the plant development. The transformation of the useful areas tested for a spacing means spacing rectangular 3.0 x 3.5 as appropriate. The SPAD index showed no differences as a function of floor area per plant